2019
DOI: 10.1101/805184
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryo-electron microscopy structure of a nucleosome-bound SWI/SNF chromatin remodeling complex

Abstract: 13The multi-subunit chromatin remodeling complex SWI/SNF 1-3 is highly conserved from 14 yeast to humans and plays critical roles in various cellular processes including 15 transcription and DNA damage repair 4,5 . It uses the energy from ATP hydrolysis to 16 remodel chromatin structure by sliding and evicting the histone octamer 6-10 , creating 17 DNA regions that become accessible to other essential protein complexes. However, 18 our mechanistic understanding of the chromatin remodeling activity is largely h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…It is important to note that this initial assembly process primarily involves evolutionarily conserved subunits and domains and is thus likely conserved for all SWI/SNF chromatin remodelers (Kadoch and Crabtree, 2015). This model is supported by the structural similarities we observe between the yeast SWI/SNF and RSC complexes (and in agreement with a recently reported structure of yeast SWI/SNF bound to a nucleosome by Han et al, 2019). In the case of RSC, assembly Figure 6.…”
Section: Model Of Rsc Core Assemblysupporting
confidence: 87%
See 1 more Smart Citation
“…It is important to note that this initial assembly process primarily involves evolutionarily conserved subunits and domains and is thus likely conserved for all SWI/SNF chromatin remodelers (Kadoch and Crabtree, 2015). This model is supported by the structural similarities we observe between the yeast SWI/SNF and RSC complexes (and in agreement with a recently reported structure of yeast SWI/SNF bound to a nucleosome by Han et al, 2019). In the case of RSC, assembly Figure 6.…”
Section: Model Of Rsc Core Assemblysupporting
confidence: 87%
“…During the submission of this manuscript the structure of SWI/SNF bound to a nucleosome was published by Han et al (2019). While at the time of final submission of this manuscript, the structure by Han et al has not been deposited yet, and a direct comparison could not be made, several clear similarities and differences are apparent.…”
Section: Author Contributionsmentioning
confidence: 99%
“…When our manuscript was under review, three related structures were reported, two structures of RSC-nucleosome complexes 29 , 30 and a structure of the yeast SWI/SNF-nucleosome complex 31 . Together, these structures provide a basis for understanding the multiple functions of SWI/SNF family remodelers in chromatin biology.…”
Section: Swi/snf Family and Cancermentioning
confidence: 99%
“…When our manuscript was under review, three related structures were reported, two structures of RSC-nucleosome complexes 29,30 and a structure of the yeast SWI/SNFnucleosome complex 31 . Together, these structures provide a basis for understanding the multiple functions of SWI/SNF family remodelers in chromatin biology.…”
Section: Swi/snf Family and Cancermentioning
confidence: 99%